Supporting Cambodian climate negotiators for COP - including Brief to the Senate - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Fellows, analysts, and trainees of the Parliamentary Institute of Cambodia together with 12 members of the Senate of Cambodia were trained in a 10-month program on parliamentary diplomacy, with an emphasis on climate change politics. This has informed Senate communication including a brief offered by the President of the Senate to the Senate assembly.